Romantic relationship dissolution on social networking sites: Self-Presentation and public accounts of breakups on Facebook. (December 2021) - Fox, Jesse; Frampton, Jessica R.; Jones, Elizabeth; Lookadoo, Kathryn
Social media users post an endless stream of life updates, commentary, and other content. This online self-presentation constitutes a narrative that can be examined as a shared account. In this study, we tested the applicability of Duck's model of relational dissolution (Duck, 1982; Rollie & Duck, 2006) to participants' personal and public accounts of their romantic breakups on social networking sites (also referred to as social network sites). We adopted mixed methods (content analysis, survey, and interview) to examine emerging adults' ( N = 97) account-making during romantic relationship dissolution and the role of social media, specifically Facebook, in the process. Over 3500 posts and comments from before and after users' breakups were quantitatively and qualitatively content analyzed. Synthesizing these three data sources revealed patterns regarding users' selective self-presentation in masspersonal channels. Their dissolution accounts were shaped by perceptions of Facebook's social affordances, such as the visibility and persistence of posts, comments, and relational artifacts; social feedback (e.g., comments and "likes" from the online social network, usually for social support); conversational control (e.g., blocking and defriending); and network association, which created a diverse imagined audience and context collapse. Findings suggest that some of Duck's relational dissolution model manifests on social media, particularly social, gravedressing, and resurrection processes. Users consider and capitalize on perceived affordances of computer-mediated communication channels to construct, curate, or avoid public accounts of their breakups. Our study also provides a methodological framework for investigating user experiences and selective self-presentation on social media over time synthesizing quantitative and qualitative methods.